#CommunicationSoWhite. (2nd April 2018) - Chakravartty, Paula; Kuo, Rachel; Grubbs, Victoria; McIlwain, Charlton
Abstract: Racial inequalities and the colonial legacies of White supremacy permeate scholarly and public discussions today. As part of an ongoing movement to decenter White masculinity as the normative core of scholarly inquiry, this paper is meant as a preliminary intervention. By coding and analyzing the racial composition of primary authors of both articles and citations in journals between 1990–2016, we find that non-White scholars continue to be underrepresented in publication rates, citation rates, and editorial positions in communication studies. We offer some analysis as to why these findings matter in our current political moment, and propose steps the field might take towards further documenting and rectifying race and representation in the production of disciplinary knowledge.